Saint Vincent and the Grenadines. Significant achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Saint Vincent and the Grenadines during 2019 are identified, with respect to the needs and interests of the country, strengthening issues of health and food safety, good agricultural practices, apiculture, agrotourism and climate resilience. As well as technical support in governance, leadership, agribusiness management, post-harvest management, seedling production. Finally, we collaborated in the training of young people in agricultural matters, as well as strengthening the collaboration of the public and private sectors.